Strategi Guru Dalam Mengatasi Perilaku Perundungan Di MTs Muhammadiyah Kabila Kabupaten Bone Bolango - Lisdayati Djafar; Lian Gafar Otaya; Anugrah Lestari (Pekerti: Journal Pendidikan Islam dan Budi Pekerti, 2025)
This research aims to find out (1) what forms of bullying behavior exist at MTs Muhammadiyah Kabila, Bone Bolango Regency (2) teachers' strategies for dealing with bullying behavior at MTs Muhammadiyah Kabila, Bone Bolango Regency (3) supporting and inhibiting factors for teachers in overcoming bullying behavior at MTs Muhammadiyah Kabila, Bone Bolango Regency. The method used is a qualitative method and a descriptive approach with data collection methods in the form of observation, interviews and documentation. The results of this research show that at MTs Muhammadiyah Kabila, Bone Bolango Regency, there are two forms of bullying behavior, the first is verbal bullying, such as mocking each other, isolating each other, making fun of friends by calling their parents' names, and saying rude things to each other. The two physically abused each other, such as pulling shirt collars, pushing and hitting each other. The teacher's strategy in dealing with bullying behavior is providing supervision, providing class-based and non-class character strengthening or what is called P5, giving advice or appeals and giving punishment. Then the supporting factors are that students want to report, there is awareness of students in participating in the character strengthening program (P5), while the inhibiting factors for teachers are that students tend to be silent and do not want to report to the teacher, students are difficult to advise and do not want to listen to the teacher, and inadequate facilities and infrastructure.